Efficacy of Triple Prophylaxis for Prevention of Graft-Versus-Host Disease in Matched Sibling Allogeneic Peripheral Blood Hematopoietic Stem Cell Transplantation in Pediatric Patients - Fernando Tienda-López; Mariana Díaz-Ruiz; Jorge Marcos-García; Óscar González-Llano; Valentine Jiménez-Antolinez (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Graft-versus-host disease (GVHD) continues to compromise the overall success of allogenic hematopoietic stem cell transplantation. It is the most important cause of morbidity and non-relapse mortality after allogeneic hematopoietic stem cell transplantation for malignant disease. In adults, post-transplant cyclophosphamide (Cy-PT) has been shown to be a feasible, economically accessible, and effective strategy to reduce the incidence of GVHD in matched sibling hematopoietic stem cell transplantation in combination with a calcineurin inhibitor plus mycophenolate mofetil (MMF). AIM: Demonstrate the clinical benefit of Cy-PT plus a calcineurin inhibitor combined with MMF for GVHD prophylaxis in HLA-matched, related peripheral blood stem cell transplants in pediatric patients with malignant hematologic neoplasms compared to standard therapy in historical controls. METHODS: A retrospective study was conducted on 22 pediatric patients with malignant hematologic neoplasms who underwent HLA-matched related peripheral blood allogenic stem cell transplantation (alloSCT) between July 2012 and December 2022. A comparison was made between two groups, one with triple prophylaxis using Cy-PT, cyclosporine (CsA), and MMF, and a historical cohort that received standard GVHD prophylaxis based on CsA and methotrexate (MTX). Patients were identified from a hospital registry. Descriptive and inferential statistics will be reported, using SPSS version 25 for analysis. RESULTS: Twenty-two patients received HLA-matched alloSCT from first-degree relatives genotypically identical in HLA-A, HLA-B, and HLA-DRB1 alleles. The demographic characteristics of both groups are summarized in the table. No patient experienced primary graft failure, sinusoidal obstructive syndrome, or hemorrhagic cystitis. Acute GVHD grade II-IV did not develop in patients who received Cy-PT, whereas in the CsA/MTX prophylaxis group, 1 (9%) grade IV patient was observed who died due to this cause before day 100. Two patients (18%) developed Moderate/Severe GVHD in the CsA/MTX group, and 1 (9%) had moderate GVHD in the Cy-PT group. Two-year overall survival was similar between the two groups (Cy-PT 53% and CsA/MTX 67%), as was event-free survival (PTCy 48% vs. CsA/MTX 61%). CONCLUSION: Peripheral blood represents a feasible option in our setting due to rapid graft engraftment, short hospital stays, and low incidence of primary graft failure, but with a higher incidence of GVHD as reported in the literature. We explored the efficacy and safety of triple prophylaxis for HLA-matched alloSCTs from peripheral blood using Cy-PT + CsA + MMF in a small group of patients, with outcomes slightly better than standard prophylaxis. These preliminary results motivate us to continue with this new regimen.